计算:【(2x-y)(2x+y)+y(y-6x)】÷(2x)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 23:28:43
计算:【(2x-y)(2x+y)+y(y-6x)】÷(2x)计算:【(2x-y)(2x+y)+y(y-6x)】÷(2x)计算:【(2x-y)(2x+y)+y(y-6x)】÷(2x)原式=(4x^2-y
计算:【(2x-y)(2x+y)+y(y-6x)】÷(2x)
计算:【(2x-y)(2x+y)+y(y-6x)】÷(2x)
计算:【(2x-y)(2x+y)+y(y-6x)】÷(2x)
原式=(4x^2-y^2+y^2-6xy)/2x=4x^2-6xy/2x=2x-3y
原式=(4x平方-y平方+y平方-6xy)÷(2x)
=2x(2x-3y)÷(2x)
=2x-3y
2x-3y
(x-2y)(x+y)+(x+y)计算
计算:(x-y)^2-(x+y)(x-y)
计算 :2(x-y)^2-(y-x)^2-(x+y)(y-x)
计算:(-x+2y)*(x-2y) (-2y+x)*(x-2y)
计算(x-y)^2×(x-y)^3×(y-x)×(y-x)^2
计算:[(x+y)³-2(x+y)²-4(x+y)]÷(x+y)
计算:y-x分之x+y+x-y分之y-y-x分之2x-y
计算:1/(2x) - 1/(x+y)((x+y)/(2x) - x - y)
计算2x/1-x+y/1·(2x/x+y-x-y)
计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)
(x+y)^2-(3x-2y)^2计算
因式分解(-x-2y)(3x-y)计算
计算(x+y)^2+10(y-x)+25
计算(2x-y)(y-2x)要有过程
(x十2y)(2x-y)怎么计算
初二下册计算:(x-y /x+2y)³
计算x^2y^-3(x^-1y)^3
计算:(x-3y)(x+2y)